Effective military multinational operations including cultural dimension - LUPU, MĂDĂLINA-ELENA (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
This article focuses on cultural awareness of military personnel starting from the premise that millennial cultures cannot be changed in the short or medium term or shouldn’t be changed by others. It begins with the cultural awareness means and with its evolution from concern to the stage of necessity, to the concept of cultural awareness and in the end to a national security priority. It addresses the cultural dimension as a part of the military operations, along with the technical part that is absolutely necessary, but not sufficient. It continues with the stage of scientific research in the field, starting from the first step that should be taken in the cultural awareness process and from the need to introduce cultural education into the military and leaders development programs and in the end it highlights the influence that culture has on state policy and that cultural dimension has on national security. It concludes that cultural awareness becomes an imperative for multinational military operations effectiveness, for a successful cooperation with allies, for close interaction between military personnel who come from different cultures, for adapting to the security changes in countries where military personnel is needed and for succeeding national security policies.